Association of serum irisin concentrations with the presence and severity of obstructive sleep apnea syndrome. Issue 5 (11th October 2016) - Li, Yanli; Li, Xueqin; Sun, Dejun; Cai, Shaoxi
Abstract : Objective: Obesity is involved in the pathogenesis of obstructive sleep apnea syndrome (OSAS). Irisin, a recently discovered myokine, protects the mice from obesity. This study aims to determine the association of serum irisin concentrations with the presence and severity of OSAS. Methods: This cross‐sectional investigation was performed in 165 male OSAS patients and 98 healthy male subjects. Serum irisin concentrations were assessed using an enzyme‐linked immunosorbent assay kit. Results: The serum irisin concentrations of OSAS patients significantly decreased compared with the healthy controls ( P <.001). Multivariable logistic regression analysis indicated that serum irisin concentrations were an independent determinant of OSAS (OR .971, 95% CI .960 to .981; P <.001). Serum irisin concentrations were significantly reduced among patients with severe OSAS compared with patients with mild and moderate OSAS ( P <.001 and P =.010, respectively). Spearman correlation analysis revealed that serum irisin concentrations were inversely correlated with OSAS severity ( r =−.327, P <.001). Conclusion: Decreased serum irisin concentrations are associated with the presence and severity of OSAS.